Prognostic significance of hemoglobin levels in patients with primary epithelial ovarian carcinoma undergoing platinumbased chemotherapy - Khemmawan Pongsanon (2018)
The aim of this study was to evaluate the prognostic impact of hemoglobin (Hb) levels before and throughout the course of platinum-based chemotherapy in patients with primary epithelial ovarian cancer (EOC). Medical records of patients who had undergone initial surgery followed by platinum-based chemotherapy for EOC were retrospectively studied. Univariate and Cox-regression models were used to evaluate the prognostic impact of various factors including Hb levels before and throughout chemotherapy in terms of overall survival. Additionally, sensitivity/specificity were calculated using receiver operating curves (ROCs) and Kaplan-Meier studies were used to determine optimal cut-off levels. The median duration of follow-up was 37.0 months. Degree of anemia before starting chemotherapy was significantly related to overall survival (p = 0.001), but the Hb level throughout chemotherapy demonstrated only a borderline relationship (p = 0.062). Only residual tumor after surgery and degree of anemia before starting chemotherapy proved to be independent prognostic factors (p = 0.013 and 0.015, respectively). With sensitivity/specificity and Kaplan-Meier analyses, a Hb level before starting chemotherapy of less than 10.5 g/dl was related to shorter overall survival (p = 0.002). In conclusion, pre-chemotherapy Hb level has a prognostic impact on overall survival in patients with EOC candidate to first-line platinum-based chemotherapy. However, the significance of decreased Hb levels during chemotherapy needs to be clarified in further prospective studies to determine optimal Hb levels for achieving a favorable outcome.